Slovak Republic : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
The government has begun implementing an ambitious program of banking sector and enterprise reform in 1999. A key aspect of this program is the restructuring and privatization of three large state-owned banks. As a by-product of the bank restructuring, the bad assets carved out from the banks will be worked out, together with tax and social security arrears. The Slovak authorities have embarked on an ambitious task to deal with inherited weaknesses of the banking system. Now the challenge is to focus on the institutional improvement in banking supervision.